THE EFFECTIVENESS OF CHUNKING AND PAUSING TECHNIQUE ON ENGLISH SPEECH FLUENCY ABILITY OF SENIOR HIGH SCHOOL STUDENTS AT SMA NEGERI 2 UNGARAN - Hardiany, Dewi Rosnita; Budiati (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2024)
Based on observations in several schools, speaking skills are considered more difficult for students to master than other passive English skills (reading and writing). Public speaking as the ability to speak well in public for students is less than optimal. Students often experience difficulties due to lack of preparation so they are not confident when doing public speaking. Another cause is excessive anxiety so that the presentation they make does not match expectations. There are several methods and techniques that can be used in making presentations or public speaking so that the presenter can produce a good performance and the material presented can be accepted by the audience, one of which is chunking and pausing techniques. This research aims to determine the effect of using Chunking and Pausing techniques on English Speech Fluency abilities for high school students in Semarang Regency area. This activity was carried out for 18 students of the English Club at SMA Negeri 2 Ungaran class X and XI by conducting a pre-test, providing material and ending with a post-test. From the results of this activity, it was found that there was a significant change in the students' speech fluency before and after being given chunking and pausing technique material, namely an increase in the fluency aspect of 2.6, the pronunciation and accent aspect of 1.3. , the vocabulary mastery aspect is 1.4, the grammar aspect is 0.4, and the details aspect is 1.3. It can be concluded that the students' ability to use chunking and pausing techniques makes their speech performance look more natural so that the level of understanding of the listener becomes better and the listener's attention becomes higher than before. Keywords: Public speaking, chunking techniques, pausing techniques